Can on-the-job training stabilize employment among rural migrant workers?. Issue 3 (5th September 2016) - Jiang, Jinqi; Zhang, Guangsheng; Qi, Diming; Zhou, Mi
Abstract : Purpose: Whether training contributes to stabilizing employment among rural migrant workers in cities remains unclear. Based on this gap in the research, the purpose of this paper is to examine how on-the-job training affects rural migrant workers' job mobility in China. Design/methodology/approach: By using randomly sampled survey data on migrant workers in Liaoning province in 2014, the authors applied a logistic model and survival analysis to explore the effect of on-the-job training on migrant workers' job turnover and understand workers' job change behaviour after receiving on-the-job training. Findings: The results showed that job training provided by employers can significantly reduce migrant workers' turnover by increasing specific human capital. By contrast, training provided by the government or migrant workers themselves focuses on increasing general human capital and thus fails to reduce job turnover. Moreover, further discussion revealed that, in the trained group, those people with a short tenure and low wage in the first job, people without any skills before migration, male migrant workers, and people that work in medium-sized and large cities have a higher probability of changing jobs. These findings suggest that to tackle the high rate of job mobility among rural migrant workers, firms should entice this labour to train by adjusting their internal training mechanisms, and local governments should subsidize firms that provide on-the-job training for rural migrant workers to help share the costs and risks of training. Moreover, for sake of reducing job changing among those trained workers, firms even should take actions to protect their labour rights of migrant workers and to ensure that they receive equal treatment to their urban counterparts. Originality/value: This paper makes three contributions to the field of job mobility in China. First, it explores the mechanism between on-the-job training and rural migrant workers' job mobility. Second, it empirically analyses the effect of on-the-job training on migrant workers' job mobility as well as the different effects of general and specific training. Lastly, its results have important policy implications for the employment stability of rural migrant workers.